Galectin-3 as a marker and mediator of endogenous inflammation and nitrosylation oxidative stress in patients with chronic heart failure - Yu. B. Shchukin; I. I. Berezin; E. A. Medvedeva; E. I. Seleznev; V. A. Dyachkov; L. N. Slatova (Российский кардиологический журнал, 2013)
Aim. To investigate the association between plasma levels of galectin-3 and parameters of endogenous inflammation and nitrosylation oxidative stress (NOS) in patients with decompensated chronic heart failure (CHF). Material and methods. In total, 197 CHF patients with myocardial infarction in medical history were divided into 3 groups: Group 1 (n=56) with Functional Class (FC) II CHF IIA; Group 2 (n=72) with FC III CHF IIA; and Group 3 (n=69) with FC IV CHF IIB. The control group (CG) included 39 healthy individuals. Plasma levels of galectin-3, 3-nitrotyrosine, low-density lipoprotein (LDL) oxidation, EC-SOD activity, interleukin-6, and high-sensitivity C-reactive protein (hsCRP) were measured. Results. In Groups 1, 2, and 3, plasma levels of galectin-3 were significantly higher than in CG: by 39% (p<0,05), 164% (p<0,001), and 428% (p<0,001), respectively. The activity of NOS increased in parallel with CHF FC: by 24% (p<0,05) in Group 1, by 81% (p<0,01) in Group 2, and by 152% (p<0,001) in Group 3. There was a strong positive correlation between galectin-3 and 3-nitrotyrosin and between galectin-3 and LDL oxidation across all three groups. The activity of endogenous inflammation also increased in parallel with CHF FC. A strong positive correlation between galectin-3 and hsCRP, as well as between galectin-3 and interleukin-6, was also observed. Conclusion. Galectin-3 levels correlate with CHF severity and are associated with the key parameters of NOS and endogenous inflammationn. Therefore, galectin-3 could be regarded as a marker and mediator of these pathological processes.